The Implementation of Field Trip in Higher Secondary Level in Sekolah Tunas Bangsa, Kubu Raya Regency - Fajar Rahmani, Eka (Jurnal Ilmiah Spectral, 2017)
This paper is written to bring awareness to principals and teachers of schools in West Kalimantan that implementing field trip as one of the options for their learning activities can be very useful and effective to achieve the learning goals. Field trip which is the excursion is an experiential learning which brings many advantages to the students, such as skill improvement, learning motivation, and self – experience on learning. The writer in this paper takes one school which is Sekolah SPK Tunas Bangsa as the school model due to its consistency in implementing the field trip. The writer discusses how the field trip programs have been conducted so far in Sekolah SPK Tunas Bangsa by interviewing the principal. The result shows the enthusiastic in learning, confidence, and independency of students improve highly after implementing the programs. It also confirmed that the learning quality and achievements are much better after conducting field trip programs.